PENEGAKAN HUKUM TERHADAP PEDAGANG KAKI LIMA YANG BERJUALAN DI TROTOAR DI KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Eko Pratama Putra; Erdianto '; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Traffic and Land Transportation has a strategic role in supporting the development of national integration as part of efforts to improve public welfare, as mandated by The 1945 Constitution of the Republic of Indonesia. Traffic and Land Transportation is used as a public service. Implementation of Traffic and Land Transportation in service activities given directly to the public and conducted by the Government, local government, legal entities, and / or community. The uses of the pavement in the city of Pekanbaru in implementation is deficient, the issue of traffic congestion is always about the problem in the community itself, where street vendors who crowded the pavement that led to the disruption of the function of the traffic, not only for motorists but also pedestrians. The purpose of this thesis namely; First, to determine the criminal enforcement against the street vendors who sell on the pavement in the city of Pekanbaru. Second, to determine the barriers of the criminal enforcement against the street vendors who sell on the pavement in the city of Pekanbaru.The type of research can be classified in the kind of sociological research (empirical), because in this study the authors directly conducted the research on the locations in order to provide a complete and clear perspective of the examined problems. This research was conducted at the Department of Transportation of Pekanbaru. The data gathering techniques in this research using observation, interview and questionnaire.From the research, there are two principal issues that can be inferred. First, the enforcement against the street vendors who sell on the pavement in the city of Pekanbaru has not been effective according to the Law Number 22 Year 2009 regarding to Traffic and Road Transportation. Second, the inhibiting factors encountered by Department of Transportation of Pekanbaru in preventing the violations of street vendors who sell in Pekanbaru City pavement is the existence of internal and external factors. The Internal factors from government, is the lack of attention to street vendors to provide a proper and strategic location, and the lack of facilities and infrastructure to support the performance of the members. External factors, lack of awareness of street vendors to comply with traffic regulationsKeywords: Enforcement - Law - Street vendors